Determinants of Academic Underachievement in Public Junior High Schools: Evidence from Kassena-Nankana East Municipality - Wasila Yakubu; Solomon Gyamerah; Jonathan Addah; Eunice Awuvafoge (International Journal For Multidisciplinary Research, 2026)
This study investigated the determinants of academic underachievement in public junior high schools in the Kassena-Nankana East Municipality of Ghana. Underpinned by Ecological Systems Theory, the study used a descriptive survey design and involved one hundred and ninety-eight (198) students and forty-eight (48) teachers randomly selected from the Municipality. The research instrument used to collect the data was a structured 5-point Likert scale questionnaires. The results indicated that factors related to students, teachers, schools, and parent/home negatively affect students’ academic performance. The study also found that student-related, teacher-related, school-related, and parent/home-related factors significantly influence students’ low academic performance in junior high schools. The study recommends a partnership among key education stakeholders to ensure a rich and conducive learning environment where all students can strive for academic excellence.